The Importance Of Mandarin Language Mastery For STT Kerusso Graduates In Global Evangelism Missions - Joshua Christian (International Perspectives in Christian Education and Philosophy, 2024)
This study focuses on the importance of Mandarin language proficiency for active students of the Kerusso Theological College (STT) in the context of global evangelism missions. The urgency of this study lies in the increasing role of foreign languages, especially Mandarin, in reaching unreached communities in various parts of the world. With a very large number of Mandarin speakers, this language ability is essential for those involved in evangelism missions, in order to build effective communication and expand the reach of the mission.The main objective of this study is to show the importance of foreign language proficiency, especially Mandarin, for active students of STT Kerusso who are involved in global evangelism missions. This study is expected to provide insight for theological educational institutions in designing a curriculum that better supports foreign language proficiency as an integral part of mission preparation. This study uses a qualitative method with an in-depth interview approach, literature study, and participant observation. Interviews were conducted with active students and alumni of STT Kerusso who have been involved in evangelism missions in Mandarin-speaking communities. The data collected were analyzed descriptively to identify key themes related to the role of foreign languages in evangelism.The results of this study are expected to provide a deeper understanding of the urgency of mastering foreign languages in global evangelism missions, as well as offer strategic recommendations for STT Kerusso in preparing its students to face the challenges of evangelism in the future.